Predictors of PTSD symptoms in brazilian police officers: the synergy of negative affect and peritraumatic dissociation - Maia,Deborah B (2011)
BACKGROUND: Exposure to traumatic events is a necessary but not a sufficient condition for the development of posttraumatic stress disorder (PTSD). Pretrauma, peritrauma and posttrauma factors interact to impact on symptom severity. The aim of the present study is to determine risk factors for PTSD symptoms in Brazilian police officers. METHOD: In a cross-sectional sample of active duty officers (n = 212), participants were asked to complete a socio-demographic questionnaire and self-report scales on affective traits, cumulative critical incident exposure, peritraumatic distress and dissociation, PTSD symptoms, and social support. Hierarchical linear regression analysis was conducted to examine predictors of PTSD symptoms. RESULTS: Variables related to negative affect, job duration, frequency of critical incident exposure, peritraumatic dissociation, and lack of social support remained significant in the final model and explained 55% of the variance in PTSD symptoms. When interaction terms were evaluated, a synergistic effect between negative affect and peritraumatic dissociation was found. CONCLUSIONS: The risk factors found in this study provide clues on how to elaborate primary prevention strategies regarding PTSD symptoms in police officers. Such initiatives may lessen the impact of repeated exposure to traumatic events on police officers over the course of their careers.